RPL in Africa -- A Very Contrasted Landscape (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
Recognition of prior learning (RPL) in Africa has progressively emerged as a strategic lever for employability, inclusiveness, and lifelong learning. Policy frameworks, pilot projects, and research initiatives reflect both the urgency and the difficulty of turning RPL into an operational mechanism for social mobility and labor market integration. Despite progress in countries such as Botswana, Eswatini, Ghana, Kenya, Tanzania, Mauritius, and South Africa, development remains uneven. Governance is often fragmented, and policy discourse frequently outpaces implementation. Cost is always an issue. Research situates African RPL at the intersection of demographic pressure, widespread informality, and persistent gender, regional, and socio-economic disparities. Large segments of the population hold substantial knowledge, skills, and competences (KSCs) acquired outside formal education and training, yet these remain invisible without robust validation systems. This invisibility restricts access to decent employment and further learning. Limited transparency tools and weak trust between education providers and employers also constrain uptake. A recurring paradox is that formal systems may produce graduates with limited labor market relevance, while non-graduates with rich experiential learning struggle to have their KSCs recognized. RPL therefore needs to be treated not only as an assessment technique but also as a social innovation for inclusion, in a context where resistance – strategic or due to misunderstanding – remains common. Related to policy, African Union instruments, African Continental Qualifications Framework (ACQF) initiatives and South African Development Community (SADC) guidance signal political intent to develop coherent approaches. The ACQF RPL Handbook for Practitioners aims to harmonize concepts, support comparability, and build mutual trust. The SADC RPL Guidelines link RPL to regional integration, highlighting labor mobility, KSC portability, and the formalization of parts of the informal economy. National policies drafted or revised in places such as Ghana, Eswatini, and Somalia embed RPL within broader education and employment strategies, with inclusiveness as a central objective: recognizing the KSCs of disadvantaged groups, offering second-chance qualification routes for early school leavers, and supporting women, migrants, and rural workers to access vocational pathways and, where feasible, higher education. Country experiences show RPL as both policy aspiration and a field of experimentation.  Across contexts, objectives cluster around three axes: employability (making skills visible and portable to address labor-market mismatch), inclusiveness (democratizing access to qualifications and reducing inequalities), and career advancement (enabling progression, promotion, and mobility, aligned with decent work principles). These aims fit wider African and international strategies, including the Continental Education Strategy for Africa and the Sustainable Development Goals. Systemic barriers persist: incomplete legislation, unresolved financing beyond donor-backed pilots, underdeveloped quality assurance, weak coordination among ministries and social partners, and low awareness among potential beneficiaries. Two lessons stand out: RPL is embedded in debates about the value of qualifications and labor-market organization, and it must be context-sensitive: importing external models without adaptation often fails, while locally grounded experiments can build legitimacy. In Africa, informal recognition is rarely enough; people know what they can do but need formal documents to break the  circle of low qualification and non-decent wages. Employer engagement and credible assessment capacity are decisive for scaling beyond pilots. Keywords: Recognition of Prior Learning (RPL), Africa, policy tool